2012
DOI: 10.1027/1015-5759/a000098
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the German Work-Related Curiosity Scale

Abstract: Curiosity, a personality trait underlying behavioral tendencies related to knowledge acquisition, learning, and thinking, can be expected to be of high relevance in the world of work. There is, however, to date no work-related curiosity measure. The present article reports results regarding the development and validation of the new 10-item Work-Related Curiosity Scale. Based on two studies, the measure had a one-factor solution, acceptable internal consistency, and expected construct validity. In Study 2, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 43 publications
5
93
0
12
Order By: Relevance
“…Referring to the literature that has been discussed earlier, curiosity facilitates learning new skills; therefore, employees with high levels of traitrelated curiosity will learn more new skills and, accordingly, adapt more efficiently to changes in their environment. Also, Pulakos et al (2000) noted that individuals who tend to display traits such as curiosity when confronted with novel situations should be less likely to perceive change as stressful and more likely to adapt more effectively, which is in line with findings from Mussel, Spengler, Litman, and Schuler (2012) who reported negative correlations between curiosity and vulnerability. Furthermore, one of the applied settings that is typical for being exposed to a changed environment is international executives and expatriates, and several authors conceptualized curiosity as a potential predictor of successful adaption and performance of expatriates (Kets de Vries & Mead, 1991;McCall, 1994;Spreitzer, McCall, & Mahoney, 1997;Van der Zee & van Oudenhoven, 2000).…”
Section: Processessupporting
confidence: 66%
“…Referring to the literature that has been discussed earlier, curiosity facilitates learning new skills; therefore, employees with high levels of traitrelated curiosity will learn more new skills and, accordingly, adapt more efficiently to changes in their environment. Also, Pulakos et al (2000) noted that individuals who tend to display traits such as curiosity when confronted with novel situations should be less likely to perceive change as stressful and more likely to adapt more effectively, which is in line with findings from Mussel, Spengler, Litman, and Schuler (2012) who reported negative correlations between curiosity and vulnerability. Furthermore, one of the applied settings that is typical for being exposed to a changed environment is international executives and expatriates, and several authors conceptualized curiosity as a potential predictor of successful adaption and performance of expatriates (Kets de Vries & Mead, 1991;McCall, 1994;Spreitzer, McCall, & Mahoney, 1997;Van der Zee & van Oudenhoven, 2000).…”
Section: Processessupporting
confidence: 66%
“…NFC nimmt in vielen Teildisziplinen der Psychologie wie der Sozial-, Motivations-, Personal-, Gesundheits-und Pädagogischen Psychologie, einen wichtigen Platz in der Erforschung und der Vorhersage von Verhalten ein (Cavazos & Campbell, 2008;Chen & Wu, 2012;Fleischhauer et al, 2010;Haugtvedt et al, 1988;Mussel, Spengler, Litman & Schuler, 2012). Große Relevanz hat das Konstrukt NFC im Bereich der Sozialpsychologie im Rahmen des Elaboration Likelihood Models (ELM; Petty & Cacioppo, 1986), in dem es als wichtiger Moderator fungiert.…”
Section: Notwendigkeit Einer Nfc-kurzskalaunclassified
“…For example, Mussel (2012) found an uncorrected correlation of .34 between curiosity and supervisory ratings of job performance and reported incremental validities over and above several cognitive and non-cognitive variables. Likewise, significant correlations with training performance , self-rated job performance (Reio & Wiswell, 2000), and career success (Mussel, Spengler, Litman, & Schuler, 2012, Study 2) have been found for curiosity. Kearney, Gebert, and Voelpel (2009) report a positive relation between need for cognition and team performance (.24).…”
Section: Introductionmentioning
confidence: 88%
“…The internal consistency was a = .86. Second, we assessed epistemic curiosity using the Work-Related Curiosity Scale (WORCS, Mussel et al, 2012). The scale was developed specifically for research and application in organizations, using a frame-of-reference approach with workrelated item content.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation